Validity of Problem Based Learning Oriented E-LAPD for Practicing Creative Thinking Skills Reaction Rate Material - Marttina Rachmawati; Rusly Hidayah (Universitas Negeri Medan, 2024)
The era of education that occurs in the 21st century places demands on students to ensure the ability to think creatively to solve various problems. Apart from that, the development of the industrial revolution 4.0 plays a role in the current generation in terms of technology and the internet. The aim of this research is to determine the validity of E-LAPD oriented Problem Based Learning (PBL) to train creative thinking skills on reaction rate material. This research uses an R&D model, one of which is ADDIE. The ADDIE development research model consists of 5 stages, namely Analyze, Design, Develop, Implement, and Evaluate, but without carrying out the Implementation stage. This validation was carried out by 3 validators, namely 2 chemistry lecturers and 1 chemistry teacher at SMA Labschool Unesa 1 Surabaya. The results of the analysis of aspect of content validity get a mode value of 4 with a valid category, while for aspect construct validity it gets a mode value of 5 with a very valid category, the results of the content and construct validity values get a mode score of ≥ 3, so E- LPAD can be declared valid. So that E-LAPD media can be used in learning.